Phylogeography and Diversity Among Populations of the Toxigenic Benthic Dinoflagellate Prorocentrum From Coastal Reef Systems in Mexico - Cembella, Allan D.; Durán-Riveroll, Lorena M.; Tarazona-Janampa, Ulrike I.; Okolodkov, Yuri B.; García-Sandoval, Ricardo; Krock, Bernd; Hörstmann, Cora; John, Uwe (Frontiers in Marine Science, 2021)
The marine dinoflagellate genus Prorocentrum Ehrenberg comprises many species occupying primarily benthic or epiphytic habitats, particularly in tropical and sub-tropical waters. Despite concerted efforts to establish phylogenetic associations, there remain unresolved issues in defining morphospecies and membership in species complexes. The study described herein addressed the inter- and infraspecific relationships of members of the Prorocentrum lima and Prorocentrum hoffmannianum species complexes (PLSC and PHSC, respectively) by applying multivariate approaches in morphotaxonomy, molecular phylogenetics and chemodiversity to establish affinities among multiple clonal isolates. Morphotaxonomic analysis showed consistency with classical morphospecies descriptors, and high variability in cell size and dimensions, but did not challenge current species complex concepts. Phylogenetic analysis of ITS/5.8S rDNA sequences from isolates from the Gulf of California, Caribbean Sea, and Gulf of Mexico coasts compared with archived global GenBank sequences served to define five consistent clades with separation of the PLSC and PHSC. Secondary structure modeling of ITS2 rRNA variation based on compensatory base changes (CBC) was effective in resolving details of the respective species complexes and even indicated putative incipient or cryptic speciation due to potential hybridization barriers. This study represents the largest (n = 67 isolates) chemodiversity analysis of polyketide-derived toxins associated with diarrheic shellfish poisoning (DSP) from a benthic dinoflagellate genus. Relative composition of some analogs (OA, OA-D8, DTX1, DTX1a, and DTX1a-D8), including two new undescribed isomers, distinguished P. lima from P. hoffmannianum sensu lato, but without clear associations with substrate type or geographical origin. Although all P. lima and most (one exception) P. hoffmannianum were toxigenic, the total cell toxin content could not be linked at the species level. This research demonstrates that clonal chemodiversity in toxin composition cannot yet be effectively applied to define ecological niches or species interactions within local assemblages. Phylogenetic analysis of the ITS/5.8 rDNA, particularly when combined with secondary structure modeling, rather than only a comparison of LSU rDNA sequences, is a more powerful approach to identify cryptic speciation and to resolve species complexes within benthic dinoflagellate groups.